1134 A morbidly obese type I diabetic teenager with sleep apnea, nocturnal eating, and Cushingoid features. Where to start?. (27th April 2018) - Hawkins, Melody N; Williams, Christopher; Kryger, Meir
Abstract: Introduction: Nocturnal eating can be dangerous in addition to causing adverse health conditions. When assessing for nocturnal eating behaviors medical etiologies must be ruled out. Report of Case: A 17-year-old male presents to the sleep clinic for nocturnal eating. His medical history is significant for obesity with a body mass index of 35.9 kg/m2 and type I diabetes mellitus under poor control requiring high doses of insulin. He has a history of obstructive sleep apnea diagnosed age 5 years treated with adenoidectomy and tonsillectomy. For the prior 3 years he developed abnormal night time behavior characterized by waking up with palpitations, night sweats, and a feeling of extreme hunger. He nightly eats an average of 4000 calories; he only sometimes remembers eating during the night. Elevated early morning glucose levels directed increasing doses of insulin. His twin sister has a diagnosis of diabetes and pituitary adenoma. On physical exam, he has extensive stria on his abdomen and back with a Cushingoid appearance. Axillary/body hair is lacking. Prior endocrine work up included a midnight salivary cortisol level obtained twice; results were not consistent with Cushing's disease. Polysomnogram was notable for a night time awakening at 2:30am with report of extreme hunger. His blood glucose was 63 mg/dL, after eating it increased to 107 mg/dL. Obstructive sleep apnea was identified with an apnea hypopnea index of 10/hour. PAP therapy was initiated. He awaits evaluation by a specialized pediatric endocrinologist and brain imaging. Conclusion: Hypoglycemic states are a suspected etiology of nocturnal eating in the setting of diabetes with elevated morning glucose levels. Chronic somogyi rebound was confirmed by documentation of hypoglycemia prior to an episode of nocturnal eating during the polysomogram. His physical findings and sibling history raise concern for hypothalamic dysfunction or pituitary disease. Obesity and sleep apnea increase insulin resistance risk warranting prompt treatment.